Pemahaman Hadis A. Hassan Dalam Perspektif Sosiologi Pengetahuan - Maula Sari (Diroyah : Jurnal Studi Ilmu Hadis, 2020)
ABSTRACThis paper aims to look at the hadith thinking of Ahmad Hassan in the sociology of knowledge. Knowledge Sociology is the study of the relationship between the human mind and the social context that influences it. Not many Muslims, especially in Indonesia, are truly experts in the field of Hadith studies. This is because this study requires perseverance and patience. The dominance of the jurisprudence of the school has prevented Muslims from interacting directly with the Koran and hadith. Ahmad Hassan appeared with Islamic reform and freedom in understanding religious teachings without being bound by a school. This writing uses Library research. Ahmad Hassan, who is known as a figure of reform or tajdid who is also known as ishlah, is very giving his thoughts in the field of hadith.Keywords: Ahmad Hassan, Sociology of Knowledge.ABSTRAKTulisan ini bertujuan untuk melihat pemikiran hadis Ahmad Hassan dalam sosiologi pengetahuan. Sosiologi Pengetahuan adalah studi mengenai hubungan antara pikiran manusia dengan konteks sosial yang mempengaruhinya. Tidak banyak umat muslim khususnya di Indonesia yang benar-benar ahli dalam bidang kajian hadis. Hal ini disebabkan karena studi ini memerlukan keuletan dan ketelatenan. Dominasi fikih mazhab telah menghalangi umat islam dalam berinteraksi dengan al-Quran dan hadis secara langsung. Ahmad Hassan tampil dengan pembaharuan Islam dan kebebasan dalam memahami ajaran agama tanpa terikat dengan suatu mazhab. Penulisan ini menggunakan Library research. Ahmad Hassan yang dikenal sebagai satu tokoh pembaruan atau tajdid ysang dikenal juga dengan ishlah sangat memberikan pemikirannya dalam bidang hadis.Kata Kunci: Ahmad Hassan,sosiologi Pengetahuan.